2022
DOI: 10.1038/s41598-022-17446-y
|View full text |Cite
|
Sign up to set email alerts
|

Ym155 localizes to the mitochondria leading to mitochondria dysfunction and activation of AMPK that inhibits BMP signaling in lung cancer cells

Abstract: The imidazolium compound Ym155 was first reported to be a survivin inhibitor. Ym155 potently induces cell death of many types of cancer cells in preclinical studies. However, in phase II clinical trials Ym155 failed to demonstrate a significant benefit. Studies have suggested that the cytotoxic effects of Ym155 in cancer cells are not mediated by the inhibition of survivin. Understanding the mechanism by which Ym155 induces cell death would provide important insight how to improve its efficacy as a cancer ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The reason for that has started to become clear only recently. It has been shown that, being a penetrating cation, it accumulates in mitochondria and binds to mitochondrial DNA, causing energy depletion in the cells [76]. Ym155 generates ROS in mitochondria, causing DNA damage and inhibiting survivin.…”
Section: Sepantronium Bromide (Ym155)mentioning
confidence: 99%
“…The reason for that has started to become clear only recently. It has been shown that, being a penetrating cation, it accumulates in mitochondria and binds to mitochondrial DNA, causing energy depletion in the cells [76]. Ym155 generates ROS in mitochondria, causing DNA damage and inhibiting survivin.…”
Section: Sepantronium Bromide (Ym155)mentioning
confidence: 99%
“…Indeed, a recent study showed that it accumulates in mitochondria and causes mitochondrial dysfunction, suggesting another potential mechanism of action for compound 1. 115 Compound 1 has a 1,4-benzoquinone containing dual carbonyl groups which is prevalent in both biological molecules and approved drugs. 116 The two carbonyl groups together with the vinyl group can form a conjugated system that appears to be stable.…”
Section: Medicinal Chemistry Of Small Molecule Survivin Inhibitorsmentioning
confidence: 99%
“…Since 1 also contains the (R 3 ) N + (halogen) − motif, it may also accumulate in mitochondria. Indeed, a recent study showed that it accumulates in mitochondria and causes mitochondrial dysfunction, suggesting another potential mechanism of action for compound 1 …”
Section: Medicinal Chemistry Of Small Molecule Survivin Inhibitorsmentioning
confidence: 99%
“…The reason for that has started to become clear only recently. It has been shown that, being a penetrating cation, it accumulates in mitochondria, binds to mitochondrial DNA causing energy depletion of the cells [66].…”
Section: Ym155mentioning
confidence: 99%